1989
DOI: 10.1007/bf00427048
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of inessential late gene expression on early meiotic events in Saccharomyces cerevisiae

Abstract: SPR3 is one of at least nine genes which are expressed in sporulating Saccharomyces cerevisiae cells at the time of meiosis I. We show below that strains homozygous for null alleles of SPR3 are capable of normal meiosis and the production of viable ascospores. We have also monitored SPR3 expression in a series of strains that are defective in meiotic development, using an SPR3:lacZ fusion carried on a single copy plasmid. beta-Galactosidase activity occurred at wild-type levels in diploid strains homozygous fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

1990
1990
1998
1998

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 62 publications
1
24
0
Order By: Relevance
“…We next monitored the ability of the das mutants to undergo premeiotic DNA synthesis and to complete meiosis. Prior studies have shown that premeiotic DNA synthesis is required for expression of meiotic genes (25,31). DNA synthesis was assessed by flow cytometric determination of the relative DNA content of cells that had been stained with propidium iodide.…”
Section: Resultsmentioning
confidence: 99%
“…We next monitored the ability of the das mutants to undergo premeiotic DNA synthesis and to complete meiosis. Prior studies have shown that premeiotic DNA synthesis is required for expression of meiotic genes (25,31). DNA synthesis was assessed by flow cytometric determination of the relative DNA content of cells that had been stained with propidium iodide.…”
Section: Resultsmentioning
confidence: 99%
“…This recipient matal MATa RES1-1/+ strain forms pale blue colonies on sporulation medium supplemented with X-Gal, because it contains a sporulation-specific reporter construction (spr3::1acZ) integrated at both chromosomal loci. Transformants that sporulated better than the recipient were expected to form darker colonies in accord with the higher levels of f-galactosidase that are produced (17,20,21).…”
Section: Resultsmentioning
confidence: 99%
“…Alternatively, cells were lysed onto nitrocellulose filters and assayed for spr3::lacZ expression (2,36,47 this study (Table 1) were constructed by standard techniques (14,19,37,40,44). Strains carrying the spr3::1acZ reporter were constructed by transplacement as described previously, using pGK11 (20,21). Haploid segregants carrying the RES1-1 mutation were detected by their ability to express the spr3::1acZ fusion at low levels, using a plate assay as described previously (21).…”
Section: Methodsmentioning
confidence: 99%
“…Cloning and characterization of a large number of the genes identified in these studies have almost invari ably revealed that they are expressed preferentially in sporulating cells (for review, see Mitchell 1994). In con trast, many of the sporulation-specific genes that were identified on the basis of their expression pattern (Clancy et al 1983;Percival-Smith and Segall 1984;Gottlin-Ninfa and Kaback 1986;Law and Segall 1988;Bishop et al 1992;Coe et al 1992) do not appear to have an essential role in the sporulation program (Garber and Segall 1986;Gottlin-Ninfa and Kaback 1986;Percival-Smith and Segall 1986;Law and Segall 1988;Kao et al 1989;Kallal et al 1990;Muthukumar et al 1993). SPSl is one of the few sporulation-specific genes isolated in a differential hybridization screen (Percival-Smith and Segall 1984) that was found to be required for spore for mation (Percival-Smith and Segall 1986).…”
mentioning
confidence: 99%